2009
DOI: 10.1021/jp9029776
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Induced Current Densities in Aromatic, Antiaromatic, Homoaromatic, and Nonaromatic Hydrocarbons

Abstract: The magnetically induced current densities for ring-shaped hydrocarbons are studied at the density functional theory (DFT) and second-order Møller-Plesset (MP2) levels using gauge-including atomic orbitals. The current densities are calculated using the gauge-including magnetically induced current approach. The calculations show that all studied hydrocarbon rings sustain strong diatropic and paratropic ring currents when exposed to an external magnetic field, regardless whether they are unsaturated or not. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
255
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(279 citation statements)
references
References 80 publications
22
255
2
Order By: Relevance
“…Jmax can be used as a measure of the bond current strength and was successfully applied in a series of recent studies. [41][42][43] Calculations of ring currents were performed using inhouse Fortran routines, GAMESS-UK [44] and SYSMO [45] .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Jmax can be used as a measure of the bond current strength and was successfully applied in a series of recent studies. [41][42][43] Calculations of ring currents were performed using inhouse Fortran routines, GAMESS-UK [44] and SYSMO [45] .…”
Section: Computational Detailsmentioning
confidence: 99%
“…24,34 There is a positive net current of the magnitude 2-5 nA/T in the phenylene rings of the nanohoops with n = 7-11. The phenylene rings are most planar in [11]CP, which can explain the improved electron delocalization in the phenylene moieties of the larger rings. Previously it was shown that benzene rings fused to antiaromatic molecules sustain a net current while the benzene rings fused to overall aromatic molecules only split the current which is delocalized over the whole molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The other dianionic nanohoops with eight or more phenylene rings have a current susceptibility strength of about 35 nA/T and possess a similar structural stabilization, while [10]CP 2-forms an exception regarding both the structure and the ring current. The largest dianionic nanohoop [11]CP 2-does display a slightly smaller bond length alternation and smaller staggering angles between the phenylene rings as compared to the neutral [11]CP, and consequently the ring current is equally divided along the edges of the phenylene rings.…”
Section: Introductionmentioning
confidence: 99%
“…The various features of the SC(6) wavefunctions for 2 and 2-TS that are displayed in Figures 5 and 6 and in Table 4 indicate that the electronic structures of both of these systems resemble that of 1,3,5-hexatriene. This finding implies that both of 2 and 2-TS are non-aromatic whereas, according to Sundholm et al, 23,34 the ring-current strength in 2, calculated using the gauge-including magnetically induced current method (GIMIC), 34 is about half the benzene value, suggesting that 2 is half as aromatic as benzene. The SC results reported here show instead that the differences between the aromaticities of 2 and benzene are much more substantial.…”
Section: Resultsmentioning
confidence: 93%